2008
DOI: 10.3810/pgm.2008.09.1920
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Obesity and Pregnancy

Abstract: Obesity is a global health problem that is increasing in prevalence. The World Health Organization characterizes obesity as a pandemic issue, with a higher prevalence in females than males. Thus, many pregnant patients are seen with high body mass index (BMI). Obesity during pregnancy is considered a high-risk state because it is associated with many complications. Compared with normal-weight patients, obese patients have a higher prevalence of infertility. Once they conceive, they have higher rate of early mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
1
7

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(67 citation statements)
references
References 0 publications
2
57
1
7
Order By: Relevance
“…Pregnancy-induced hypertension is a maternal hypertension syndrome diagnosed during the later part of pregnancy, usually after the 20th week of gestation (10). Due to the prompt aggravation of the function of the kidneys and heart, it was suggested that the pregnancy-induced hypertension in the present study may have resulted from ATRA management.…”
Section: Discussionmentioning
confidence: 76%
“…Pregnancy-induced hypertension is a maternal hypertension syndrome diagnosed during the later part of pregnancy, usually after the 20th week of gestation (10). Due to the prompt aggravation of the function of the kidneys and heart, it was suggested that the pregnancy-induced hypertension in the present study may have resulted from ATRA management.…”
Section: Discussionmentioning
confidence: 76%
“…Those that conceive have increased rates of sporadic miscarriages 10,11 and congenital anomalies including neural tube defects. 12 In pregnancies that progress weight loss is discouraged 13 In pregnancy the complications include pre-eclampsia/eclampsia, 3 iatrogenic preterm delivery and post-dates. 12,14 The babies have the risks of polyhydramniosis, macrosomia and intra-uterine deaths.…”
Section: Complications Of Obesitymentioning
confidence: 99%
“…12,14 The babies have the risks of polyhydramniosis, macrosomia and intra-uterine deaths. 3 The rates of induction of labour are high due to post-dates and macrosomic foetuses. During labour there are difficulties in sigthing intravenous canulae and epidural anaesthesia.…”
Section: Complications Of Obesitymentioning
confidence: 99%
See 2 more Smart Citations